In North-Eastern India... Gerbera in open field cultivation is promising - Keditsu, Rokolhuii (Indian Horticulture, 2019)
Exploiting the prevailing growing conditions (planting time) and maintaining water-nutrient synergy through an integrated nutrient supply system across crop phenophases are considered as the two most important aspects of gerbera cultivation. If addressed to their potential, these are supposed to bring some discernible changes in overall scenario of gerbera cultivation in northeast India, especially in Nagaland.